Prevention of COVID-19 in pregnant women, eventual use of new vaccines - Cuadra-Sánchez, César; Rivero, Alexandra; Cabrera, Carlos; Faneite, Pedro; Vigil-De Gracia, Paulino (Gaceta Médica de Caracas, 2021)
Pregnant women who have COVID-19 have an increased risk of hospitalization and death; however, there are many restrictions for the application of COVID-19 vaccines on pregnant patients, mainly because there is no confirmation of the safety of their use during pregnancy. None of the vaccines approved to date are based on live attenuated SARS-CoV-2, so the possibility of generating an infection in the fetus is nonexistent.